AKTIVITAS DAN STABILITAS RADICAL SCAVENGING L-ASKORBIL PALMITAT HASIL SINTESIS SECARA ENZIMATIK [Activity and Stability of Radical Scavenging of L- Palmitate Synthesized Enzymatically] - Tri Agus Siswoyo; Tri Ardiyati (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2009)
L-ascorbyl palmitate (AsA-Pal-Enz) was synthesized by using an immobilized lipase from Aspergillus niger. A comparison of antioxidative effects between L-ascorbic acid (AsA) and AsA-Pal-Enz was determined in terms of 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical-scavenging. The results indicate that the AsA-Pal-Enz was effective in preventing lipid oxidation, while the antioxidative activity in authentic AsA-Pal was lower. The activity of AsA-Pal-Enz was very stable than AsA-Pal standard during heating.